Optimizing Budget Allocation: A Strategic Framework for Aligning Human Resource Investments with Financial Objectives and Business Goals - Suwarno, Suwarno; Fitria , Fitria; Azhar, Rudi (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2023)
This study explores the strategic framework for aligning human resource (HR) investments with financial objectives and broader business goals to enhance organizational performance. Through a qualitative literature review, this research synthesizes existing literature to understand the dynamics between strategic HR management, financial planning, and organizational outcomes, thereby elucidating how strategic alignment can optimize budget allocation in HR. The research methodology encompasses a comprehensive review of scholarly articles, foundational texts, and empirical studies related to strategic human resource management (SHRM). The focus is on how integration of HR functions with organizational strategies can contribute to enhanced financial performance and competitive advantage. By examining studies from the past three decades, this review highlights how effectively aligned HR practices support not only immediate operational goals but also long-term strategic objectives. Findings indicate that organizations demonstrating a high degree of strategic alignment in HR practices, such as recruitment, training, and compensation, see improved financial outcomes and organizational agility. The study reveals that investments in HR are most effective when meticulously aligned with an organization's strategic vision, emphasizing the importance of a dual approach where HR not only supports but actively drives strategic decisions. Furthermore, the integration of advanced analytics and technology in HR processes emerges as a significant enhancer of this alignment, enabling more precise decision-making and real-time adjustments in strategy. This research contributes to the existing body of knowledge by providing a detailed analysis of the mechanisms through which strategic HR alignment impacts organizational performance and by proposing a framework for organizations to optimize their HR budget allocation in line with strategic goals.